The Influence of Service Quality on Student Satisfaction and Implications for Loyalty Lessee Loyalty (Study on Learners at Vocational High School (SMK) Negeri 1 Soreang) - Kosasih, Ade; Febrian, Feby; Mulyana, Agus (Greenation International Journal of Engineering Science, 2024)
This study aims to provide an overview of service quality, student satisfaction, and student loyalty among students at Vocational High School (SMK) Negeri 1 Soreang. Additionally, it seeks to determine the direct and indirect effects of service quality on student satisfaction and loyalty, as well as analyze the impact of student satisfaction on student loyalty. The research method used in this study is a causal associative approach, which examines the relationship between variables that have a causal connection. The sampling technique applied is non-probability sampling, specifically purposive sampling. The unit of analysis is the students of SMKN 1 Soreang, Bandung Regency, with a sample size of 56 students. The results indicate that service quality, student satisfaction, and student loyalty at SMK Negeri 1 Soreang are in good, satisfactory, and loyal conditions, respectively. Moreover, service quality has a positive and significant effect on both student satisfaction and loyalty. Similarly, student satisfaction positively and significantly influences student loyalty. Since both service quality and student satisfaction impact loyalty, it was found that student satisfaction has a more dominant influence. Therefore, enhancing student satisfaction should be the top priority in improving student loyalty. It is recommended that SMKN 1 Soreang focuses on increasing the sense of satisfaction among its students by delivering high-quality services, thereby fostering greater loyalty to the school.